2009
DOI: 10.1016/j.cub.2008.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Motor- and Tail-Dependent Targeting of Dynein to Microtubule Plus Ends and the Cell Cortex

Abstract: Summary Background Cytoplasmic dynein mediates spindle positioning in budding yeast by powering sliding of microtubules along the cell cortex. Although previous studies have demonstrated cortical and plus-end targeting of dynein heavy chain (Dyn1/HC), the regulation of its recruitment to these sites remains elusive. Results Here we show that separate domains of Dyn1/HC confer differential localization to the dynein complex. The N-terminal tail domain targets Dyn1/HC to cortical Num1 receptor sites, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
175
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(194 citation statements)
references
References 36 publications
(57 reference statements)
14
175
4
Order By: Relevance
“…This inability to move is consistent with the in vivo microtubule decoration phenotype ( Figure 1B; Figure 2A) and the nucleotide-insensitive microtubule-binding phenotypes ( Figure 6, A and B). Our studies were the first to examine the AAA3 Walker B E/Q mutation in a whole dynein molecule, and our results are in general agreement with previous studies that showed increased MT-binding affinity and altered dynein localization in fruit fly and budding yeast (Silvanovich et al 2003;Cho et al 2008;Markus et al 2009). For example, one study showed that UV-vanadate cleavage occurred at levels equal to wild-type strains (Silvanovich et al 2003).…”
Section: ; Ori-mckenney Et Al 2010) When We Examined Beadssupporting
confidence: 91%
“…This inability to move is consistent with the in vivo microtubule decoration phenotype ( Figure 1B; Figure 2A) and the nucleotide-insensitive microtubule-binding phenotypes ( Figure 6, A and B). Our studies were the first to examine the AAA3 Walker B E/Q mutation in a whole dynein molecule, and our results are in general agreement with previous studies that showed increased MT-binding affinity and altered dynein localization in fruit fly and budding yeast (Silvanovich et al 2003;Cho et al 2008;Markus et al 2009). For example, one study showed that UV-vanadate cleavage occurred at levels equal to wild-type strains (Silvanovich et al 2003).…”
Section: ; Ori-mckenney Et Al 2010) When We Examined Beadssupporting
confidence: 91%
“…Exactly how a tail mutation would affect dynein motor function is unclear at this point. It has been postulated that the budding yeast dynein tail may interact with the motor domain in a way that the tail would be "masked" in the presence of the motor domain (78,79). Interestingly, although the dynein regulator LIS1 binds to the motor domain at AAA3/AAA4 (26), removal of the tail appears to enhance dynein-LIS1 interaction (26,31,78).…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the budding yeast dynein tail may interact with the motor domain in a way that the tail would be "masked" in the presence of the motor domain (78,79). Interestingly, although the dynein regulator LIS1 binds to the motor domain at AAA3/AAA4 (26), removal of the tail appears to enhance dynein-LIS1 interaction (26,31,78). Given that the dynein HC is involved in multiple protein interactions (14 -18, 21-26), it remains to be tested whether the HC tail affects dynein function directly through regulating the motor domain or indirectly through coordinating the functions of other dynein regulators.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypes and the observed onset of pulling, when a cMT slides along the hyphal cortex, described by the same authors, support a mechanism for cortical pulling known from studies in S. cerevisiae. The dynein/dynactin complex is believed to be inactive while transported either by the kinesin Kip2 toward the cMT plus ends or directly recruited to plus ends from the cytoplasm (Markus et al, 2009;Roberts et al, 2014). When the cMT plus end associates with a cortical Num1 patch during sliding at the plasma membrane, the dynein/dynactin complex is off-loaded, anchored with the amino-terminal tail of Dyn1, the dynein heavy chain, to the amino-terminal binding domain of Num1, and the dynein motor is activated to eventually pull on the cMT on which it was previously hitchhiking (Lee et al, 2003;Moore et al, 2009;.…”
Section: Nuclear Movements Require An Adapted Density Of Cortical Ancmentioning
confidence: 99%